Chemical vapor deposition growth of β-Ga2O3 on Si- and C- face off-axis 4H-SiC at high temperature - Akyol, Fatih; Ozden, Hamdin (ELSEVIER SCI LTD, 2024)
Realization of beta-Ga2O3 on a high-thermal-conductivity substrate is crucial to overcome the poor thermal conductivity of beta-Ga2O3 which is one of the major roadblocks against its era in power electronics. We investigated low-pressure chemical vapor deposition (LPCVD) growth on both Si and C- face (0001) 4H-SiC at a high growth temperature of 925 C-degrees using Ga metal and O-2 gas source. Growths on C -face 4H-SiC resulted polycrystalline beta-Ga2O3 for the entire O-2 -flow range, whereas under optimized O-2 -flow conditions, step flow growth of (-201) beta-Ga2O3 was achieved on Si -face 4H-SiC with 3.7 nm rms surface roughness and rocking curve FWHM of 0.54(degrees) at a growth rate reaching 2.48 mu m/h 4 degrees off -axis nature of the substrate promoted the growth of some of the in -plane rotational domains while suppressing others. Raman measurements further verified the pure beta-Ga2O3 nature of the grown films. Using a customized LPCVD with solid source Ga, a costeffective, safe and industrially scalable method was shown to pave the way to enable beta-Ga2O3 heteroepitaxy on 4H-SiC for high -power electronics.
Keywords: HETEROEPITAXIAL GROWTH; MOCVD; Engineering; Materials Science; Physics